Secondary raw materials market creation: Waste stock exchange - Francesca Coda Canati (Fondazione Eni Enrico Mattei (FEEM), 2000)
The purpose of this paper is to point out the necessity to use new instruments for an integrated waste management system. Waste Stock Exchange is an innovative and efficient instrument, if introduced in a solid legal and economic context, as is typical of a free and competitive market. The Waste Stock Exchange Project is going to create a Web-based secondary raw materials market that solves logistical and qualitative problems for all public and private entities that could potentially use some kind of waste in their production cycles, or that implement recycling and recovery programs.
Keywords: G15; Q2; Q20; Q24; Q42; 330; Exchange; secondary raw materials; telecommunication; recycling; recovery; Kreislaufwirtschaft; Produkt-Recycling; Theorie; Italien; EU-Staaten